Kelayakan Finansial Fasilitas Parkir Pasar Aceh Berdasarkan Qanun Kota Banda Aceh - Rahmat Djamaluddin; Edi Mawardi (Universitas Teuku Umar, 2018)
Off Street Parking building in Pasar Aceh Baru is one of the parking facilities available in the area. Withthe increase of visitors to Pasar Aceh Baru, the need for parking space is also increasing. In this case the authors want to analyze the feasibility in terms of finance based on parking rates using Qanun Banda Aceh City No. 4 year 2012. The objective of the study is to calculate the number of parking vehicles, vehicles accumulation and to see the financial feasibility level of the parking facilities based on Laws Banda Aceh city regulated by Qanun No. 4 year 2012, so the results obtained when the parking facility has a period of turnover point of payback (Payback Period). This study uses 3 methods, namely NPV, BCR and IRR and discount rate of 10%, 12%, 15% and 18%. From the data processing using 3 methods, resulted in Net Present Value (NPV) largest value is Rp. -3,853,539,000, - at 10% discount rate while the Benefit Cost Ratio (BCR) is 0,809 at discount rate 10% and IRR value equal to -1,149%. This proves that with parking rates using Qanun Banda Aceh City No. 4 year 2012 the parking facilities are not feasible to be built financially. Keywords: Financial Feasibility, Parking Rates, NPV, BCR, and IRR